Determination of biogenic amine - content of natural wines - Kállay, M.; Sárdy, D. (International Journal of Horticultural Science, 2003)
Nowadays the consumption of natural wines has been increased. In parallel with the higher demand, the study of the parameters of natural wines has also developed. The amines being produced during the decarboxylization procedure of amino acids could be one of the most important features of natural wines. The objective of this study was to measure the biogenic amine content of natural wines from 2000 and 2001. We have determined that the biogenic amine content of natural wines is not different from the biogenic amine composition of normal wines. There was not any considerable difference between the years. In complience with the average tendency, red wines contain higher histamine-, tiramine- and serotonin values than white wines.